PENGARUH RASIO TEPUNG BERAS DAN AIR TERHADAP KARAKTERISTIK KULIT LUMPIA BASAH [Effect of Flour to Water Ratio on Characteristics of Fresh Rice-Based Spring Rolls Wrappers] - Anna Ingani Widjajaseputra; . Harijono; . Yunianta; Teti Estiasih (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
Flour to water ratio in batter compositions affected water availability which was needed to provide physical and chemical changes during fresh rice-based spring rolls wrappers processing, such as gel forming of starches and heat-induced gels, flour’s components interactions in batter systems. Degree of water-starch, water-protein and protein–starch-water interactions were depend on water amount, temperature and duration of heating. The mechanical strength of spring rolls wrappers is one of problems when it is being used. The wrappers could be torn apart due to moisture absorption from the filling and the environment. The goal of this study was to determine the optimum flour to water ratio in formulation of fresh rice-based spring rolls wrappers. The investigation was provided by Randomized Completely Block Design with single factor and three replicates. The factor was rice flour to water ratio in six levels (3.0:4.5; 3.0:5.0;3.0:5.5; 3.0:6.0; 3.0:6.5; and 3.0:7.0) the data were analyzed by Analysis of Variance with 95% degree of confident. Flour to water ratio greatly influenced elongation at break which is important in the utilization of fresh rice-based spring rolls wrappers. Its ratio also influenced the size of swelled rice starch granules, pores size and moisture content of the products. Optimal ratio flour to water is 3.0:6.0 which produced the highest elongation at break.